A linguagem idiomática da guitarra de Toninho Horta: concepções harmónicas nas música instrumental - Leandro Alves Do Carmo (2017)
The present study aims to transcribe and analyze some Toninho Horta’s compositions and arrangements, systematizing the information in compliance with popular music school agreements, in the musical performance research line. This demand arises from the opening of new university courses in Brazil, which aimed to train professionals, researchers and performers, specialized in popular music. These courses demand specific forms of popular music writing associated with acoustic and electric guitar. Our analyses will focus on the harmonies and melodies of Horta. We will research possible patterns in voice leading, harmonic progressions and rhythmic components. It will also examine how these aspects influence in composition and performance, investigating how they can help the performer in its construction.